A Nonlinear Stability Analysis of Rotating Navier-Stokes-Voigt Fluid Heated from Below - Sharma, Sweta; Sunil; Sharma, Poonam (Journal of Applied Nonlinear Dynamics, 2026)
The nonlinear and linear approach, as well as a fully nonlinear energy argument, are used to thoroughly examine the thermal convection of simultaneously rotating Navier-Stokes-Voigt fluid for three distinct bounding surfaces. It is observed that the same critical Rayleigh number is obtained using both nonlinear and linear analyses, which ensures the absence of sub-critical instability. A nonlinear energy argument describes the important role of the Kelvin-Voigt parameter in energy decay, whereas the parameter doesn’t affect the value of the Rayleigh number. The vertical fluid motion slows down due to rotation; thus, rotation postpones the onset of instability. Also, discussed the stability of Navier-Stokes-Voigt fluid contained in three different combinations of bounding surfaces.